Elucidating the Antimycobacterial Mechanism of Action of Decoquinate Derivative RMB041 Using Metabolomics - Kirsten E. Knoll; Zander Lindeque; Adetomiwa A. Adeniji; Carel B. Oosthuizen; Namrita Lall; Du Toit Loots (MDPI AG, 2021)
Tuberculosis (TB), caused by Mycobacterium tuberculosis (Mtb), still remains one of the leading causes of death from a single infectious agent worldwide. The high prevalence of this disease is mostly ascribed to the rapid development of drug resistance to the current anti-TB drugs, exacerbated by lack of patient adherence due to drug toxicity. The aforementioned highlights the urgent need for new anti-TB compounds with different antimycobacterial mechanisms of action to those currently being used. An N-alkyl quinolone; decoquinate derivative RMB041, has recently shown promising antimicrobial activity against Mtb, while also exhibiting low cytotoxicity and excellent pharmacokinetic characteristics. Its exact mechanism of action, however, is still unknown. Considering this, we used GCxGC-TOFMS and well described metabolomic approaches to analyze and compare the metabolic alterations of Mtb treated with decoquinate derivative RMB041 by comparison to non-treated Mtb controls. The most significantly altered pathways in Mtb treated with this drug include fatty acid metabolism, amino acid metabolism, glycerol metabolism, and the urea cycle. These changes support previous findings suggesting this drug acts primarily on the cell wall and secondarily on the DNA metabolism of Mtb. Additionally, we identified metabolic changes suggesting inhibition of protein synthesis and a state of dormancy.